Thermodynamics of berenil binding to polyd(AT)timespolyd(AT) and polyd(A)timespolyd(T) duplexes - Lah, Jurij (Acta chimica slovenica, 2001)
Thermodynamics of berenil binding to poly?$d(AT)\cdotpolyd(AT)$? and ?$polyd(A)\cdotpolyd(T)$? duplexes in neutral buffer solutions was studied using a combination of calorimetric and spectroscopic techniques. The resulting thermodynamic binding profiles show that berenil binding to ?$polyd(AT)\cdotpolyd(AT)$? is governed by about equal and entropic forces whereas its binding to ?$polyd(A)\cdotpolyd(T)$? is overwhelmingly entropy driven.
Keywords: berenil; DNA; molecular biology; molekularna biologija; polinukleotidi; termodinamika; vezava